2011
DOI: 10.1186/2042-4280-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human cytomegalovirus in motile spermatozoa and spermatogenic cells in testis organotypic culture

Abstract: BackgroundThe presence of human cytomegalovirus (HCMV) in male genital tract suggests its vertical transmission with spermatozoa and the development of a potentially dangerous fetal infection. The objective of the present study was to evaluate the possibility of intracellular HCMV localization in male germ cells and to examine the effect of the virus on human spermatogenesis.MethodsSemen samples from 91 infertile and 47 fertile men were analyzed. HCMV was detected by real time PCR, rapid culture method and PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
3
17
1
8
Order By: Relevance
“…In some infected cells, we found an equatorial pattern of staining similar to the attachment site described for human papillomavirus (Foresta et al ., ). It has previously been shown that CMV can infect spermatogonia, spermatocytes and spermatides in human testis organotypic culture (Naumenko et al ., ). To our knowledge, this is the first report of successful CMV infection of spermatozoa in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…In some infected cells, we found an equatorial pattern of staining similar to the attachment site described for human papillomavirus (Foresta et al ., ). It has previously been shown that CMV can infect spermatogonia, spermatocytes and spermatides in human testis organotypic culture (Naumenko et al ., ). To our knowledge, this is the first report of successful CMV infection of spermatozoa in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…Asymptomatic shedding from the genito-urinary tract was reported mainly for dsDNA eukaryotic viruses of the Adenoviridae, Herpesviridae, Papillomaviridae and Polyomaviridae families with the exception of ssDNA viruses of the Anelloviridae family [83,106,107,108,109,110,111]. In the case of polyomaviruses, it appears that viral excretion was correlated with the host immune status.…”
Section: Exploring the Viral Flora In Humansmentioning
confidence: 99%
“…In this case it appears that some herpesviruses, such as human Herpesvirus 6 A/B or the Cytomegalovirus, were able to attach to the sperm head with an intact acrosome [108,113]. Thus, given the potential risk some herpesviruses may represent to the newborns, additional research is required to evaluate the impact of this asymptomatic shedding from herpesvirus-positive donor semen.…”
Section: Exploring the Viral Flora In Humansmentioning
confidence: 99%
“…HSV and another member of the Herpesviridae, human cytomegalovirus (CMV), were found to replicate and cause damage to somatic and germ cells in testis organotypic culture (Naumenko et al . ,b). Despite the significance of these observations, it remains unclear whether HSV can cause testicular infection in vivo .…”
mentioning
confidence: 99%